Frustration The Works & It's Atonement At Almutazela - Safe, Ali (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
We concentrate in this research on a question which relates the two principles: justice & ( the promise & warning) , which is the question of frustration of work & falling it , it means a measure of human works value . The problem focus on the retires view for the interest of (Favors & Bad works ) through comparison of liabilities positions of ( Ashaera & Imamiah ). This research consist of : Introduction , conclusion & six main parts . The first part is the terminological meaning of (Frustration &Penance) , those concepts mean falling . The second part : discusses the problem in Almutazela's thought , within two positions : the first one is the position of (Abu Ali Aljeba'ee) who said in frustration& penance with the pure sense . The second position is the position of (Abu Hashem Aljeba'ee) how compares between the two meanings : ( Reward & Punishment ) , and the victories of the most a preponderance in comparison of the lowest preponderance . The Third & Forth part concentrates on Almutazela intellect & transportism evidences on the frustration and atonement and the evidences of the liabilities on the same question .